Efficacy of rhizobium strains and biofertilizers for controlling foot and root rot and increasing green pod yield of bush bean (Bangladesh Journal of Agricultural Research, 2009)
The experiment was conducted during 2002-03 in the infested plot of the BINA sub-station at Ishurdi, Pabna to evaluate the effectiveness of Rhizobium strains and biofertilizers in controlling the foot and root rot disease, and to increase green pod yield of Bush bean under field condition. The highest germination (91.6%) was recorded with BINAR P36, which was statistically similar to BAUR 107, BARIR 7029, BARIR 1000, BINAR P6 and BINA biofertilizer. The lowest germination (77.9%) was found in untreated control. The highest foot and root rot (24.5%) was observed in untreated control and the lowest (10.00%) was in BINAR P36. Biofertilizers and Rhizobial strains decreased foot and root rot upto 59.2% over untreated control. The highest green pod yield (20.8 tlha) was obtained for using BINAR P36, which was followed by BARIR 7029, BARIR 892, BARIR 1000, BINAR P6 and BINA biofertilizer. The lowest green pod yield (13.6 tlha) was found in untreated control. Rhizobium strain BINAR P36 may be used as seed treatment for controlling foot and root rot and increasing green pod yield of Bush bean. Key Words: Rhyzobium, biofertilizers, foot and root rot, bush bean. doi: 10.3329/bjar.v33i4.2305 Bangladesh J. Agril. Res. 33(4) : 617-622, December 2008